Existence results for fractional p-Laplacian systems via young measures - Balaadich, Farah; Azroul, Elhoussine (Mathematical Modelling and Analysis, 2022)
In this paper, we show the existence result of the following fractional p-Laplacian system                              for a given datum f. The existence of weak solutions is obtained by using the theory of Young measures.